Synthesis of Ag nanoparticles-decorated on CNTs/TiO2 nanocomposite as efficient photocatalysts via nanosecond pulsed laser ablation. (November 2022) - Alheshibri, Muidh; Elsayed, Khaled; A.Haladu, Shamsuddeen; Musa Magami, Saminu; Al Baroot, Abbad; Ercan, İsmail and Ercan, Filiz and A.Manda, Abdullah and Çevik, Emre and Kayed, T.S. and Alsanea, Aamerah A and Mujawwil Alotaibi, Amjad and L.Al-Otaibi, Amal
Highlights: Synthesis of silver nanoparticles decorated on CNTs/TiO2 nanocomposite by nanosecond pulsed laser ablation method. The proposed method is able to prepare an efficient visible light-induced photodegradation methylene blue dye. Complete degradation of the methylene blue dye is achieved in 50 minutes. Abstract: A simple, reproducible, and non-surfactant self-templating approach was developed for the synthesis of silver nanoparticles decorated on CNTs/TiO2 nanocomposite via a nanosecond pulsed laser ablation method. In addition, the effective use of the resulting nanocatalysts was carried out in the enhanced photocatalytic degradation of methylene blue dye contaminant. Following the synthesis of the nanocomposite catalysts, their morphology, heterostructure, and the nature of incorporation of their constituents were confirmed by TEM and SEM microscopy. In addition, characteristic diffraction patterns of the materials were studied by XRD powder diffraction method, confirming the crystalline nature of the nanocatalysts. The photoluminescence (PL) analysis provided information about the surface defects present as well as the electron-hole recombination properties of the prepared nanocatalysts. Despite the poor ultraviolet light absorption of the neat CNT and the TiO2 constituents beyond 400 nm, an efficient ultraviolet light-induced photodegradation of the methylene blue dye was successfully achieved. In this, by carrying out 50 min of ultraviolet light irradiation of the dye in the presence of the TiO2 /CNT and the Ag/TiO2 /CNT nanocomposite catalysts, 89.8% and 96 % reduction efficiencies were achieved, respectively. The experimental error associated with the photodegradation efficiency was within ± 3%. The ultraviolet light-induced catalytic degradation of the dye follows first-order reaction kinetics, with rate constants of 3.95 x10 -2 min −1 and 4.56 × 10 -2 min −1 associated with the TiO2 /CNT and the Ag/TiO2 /CN catalyzed reactions, respectively.